Language Attitude of Indonesian Workers in Cruise Ship Holland America Line - Williandani, Mega; Ningsih, Rahayu; Silalahi, Mey Ramenawati (Association of Language Teachers in Southeast Asia (ALTSA), 2020)
The term of language attitude is the feeling how people can respond to another language. This research explored the language attitude of Indonesian workers in Cruise Ship Holland America Line (HAL). It was aimed to investigate the characteristic of language attitude by Indonesian workersÃ¢â‚¬â„¢ especially in food and beverage department. The research use theory fromÃ‚Â GarvinÃ‚Â andÃ‚Â MathiotÃ‚Â (1968) there have three characteristics of language attitudes, language loyalty, pride of language, awareness of the language norm. This research conducted with descriptive qualitative research. The data of this study are the utterances of Indonesian workers in Cruise Ship Holland America Line (HAL). The source of data of this study was ten Indonesian workers at the food and beverage department. Interview was used to obtain the data. The result found that from ten participants, eight Indonesian workers showed negative language attitudes. The others have positive toward the Indonesian language. Realization of positive language attitudes influenced by friendship and place domain. Meanwhile, there were loyal to the Indonesian language by an informal situation to avoid negative thinking and respect each other among workers.